2020
DOI: 10.1002/pon.5393
|View full text |Cite
|
Sign up to set email alerts
|

Brief training in psychological assessment and interventions skills for cancer care staff: a mixed methods evaluation of deliberate practice techniques

Abstract: Objective: Unaddressed anxiety and depression is common among cancer patients and has significant adverse consequences. Cancer staff training is recommended for psychological assessment and interventions to address depression and anxiety, to increase access to psycho-social oncology care. However, psychological skills training has a poor track-record for improving clinical effectiveness. "Deliberate practice", receiving feedback on therapeutic micro-skills and rehearsing modifications, can enhance clinical eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The training offered was a development of Barrett Naylor et al.’s 20 deliberate practice model. An initial training day was offered with half the day focused on assessment skills and half focused on intervention skills.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The training offered was a development of Barrett Naylor et al.’s 20 deliberate practice model. An initial training day was offered with half the day focused on assessment skills and half focused on intervention skills.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of similar training have been unclear about durability of effects in routine practice (e.g., 20 ). This study suggests that effects can be retained for several months, but also indicates that a 1-day training may not be sufficient for longer-term skill acquisition.…”
Section: Relationship To Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…theravue.com. The notion that DP might help improve trainees' therapy skills has received some experimental support [22][23][24][25][26][27] but the evidence for an impact of DP on client outcomes is, to date, indirect [e.g., 28]. Indeed, meta-analyzing DP in diverse fields, Macnamara and colleagues [29,30] found that DP had a limited influence on performance in low-predictability environments, that is, performance settings in which the range of possible actions is high and…”
Section: Introductionmentioning
confidence: 99%
“…True, the current evidence shows DP is more effective than traditional approaches for teaching and training therapists (Barrett-Naylor et al, 2020;Newman et al, 2022;Westra et al, 2021). Still, much remains unknown and subject to revision; for example,…”
mentioning
confidence: 99%